A new cypridopsine genus (Crustacea, Ostracoda) from Thailand - Savatenalinton, Sukonthip (European Journal of Taxonomy, 2020)
A new cypridopsine genus, Cyprettadopsis gen. nov., described here, is principally characterized by the reduced caudal ramus, the strongly serrated claw G2 of the antenna (A2), the A2 subquadrate terminal segment, the undivided penultimate segment of the second thoracopod (T2), the morphology of the third thoracopod bearing a distinctly separated terminal segment, the complete septa on the posteroventral margin and the incomplete septa on the anterior margin of both valves. Based on a combination of these characters, a new tribe, Cyprettadopsini trib. nov., is created in the subfamily Cypridopsinae Kaufmann, 1900 to accommodate this new genus, and one new species, Cyprettadopsis sutura gen. et sp. nov., is described as the type species. Apart from the above generic characters, the following features are also typical of the new species: the tiny needlepoint-like pores along the anterior and ventral margins of both valves, the remarkably large β-seta on the mandibular palp and the considerably short d2 seta on the T2. The presence of marginal septa in the new genus is a distinctive character and constitutes the first record of this feature within Cypridopsinae. The taxonomically relevant characters in the new taxon and related taxa are briefly discussed.